FENOMENA PENCARI SUAKA DAN PENGUNGSI ETNIS ROHINGYA DI INDONESIA - Hamdi, Muhammad Arief; Maulidia, Hanifa; Firlana, Habbi (Polteknik Imigrasi, 2023)
Crimes against humanity in the world are still happening today, this has caused anxiety for the people of that country, as a result they are looking for a safe place to live and seeking protection in certain countries. Indonesia has become one of the destination countries for refugees and asylum seekers, especially for ethnic Myanmar Rohingya refugees, before they get a safe place based on UNHCR recommendations, therefore this study aims to analyze how the Indonesian government's policy towards international refugee migration in Indonesian territory and the process efforts made by Indonesia to tackle the migration of Rohingya refugees to Indonesian territory, especially in the province of Aceh. This study used a qualitative research method with a literature study approach and a case approach and obtained information from informants who were able to provide information related to the case, with the results of the research that the handling of Rohingya refugees in Aceh Province experienced positive progress shown by the Indonesian government. The existence of the Aceh Customary Sea Law or Panglima Laot obliges all fishermen in Aceh to help anyone whose life is threatened at sea. In addition, the people of Aceh have consistently accepted refugees while others have rejected their arrival. That there is solidarity between Muslims, with 98% of the people of Aceh identifying themselves as Muslims. The author also considers that the people of Aceh care more about human rights than the country of origin of the asylum seekers or refugees.